The joint impact of habitual exercise and glycemic control on the incidence of chronic kidney disease (CKD) in middle-aged and older males - Ryoma Michishita; Takuro Matsuda; Shotaro Kawakami; Satoshi Tanaka; Akira Kiyonaga; Hiroaki Tanaka; Natsumi Morito; Yasuki Higaki (Komiyama Printing Co. Ltd, 2017)
Abstract Background This retrospective study evaluated the influence of the joint impact of habitual exercise and glycemic control on the incidence of chronic kidney disease (CKD) during a 6-year follow-up period in middle-aged and older males. Methods The study population included 303 males without a history of cardiovascular disease, stroke, renal dysfunction, or dialysis treatment. Their lifestyle behaviors regarding exercise and physical activity were evaluated using a standardized self-administered questionnaire. The participants were divided into four categories according to the performance or non-performance of habitual exercise and the presence or absence of hyperglycemia. Results After 6 years, 32 subjects (10.6%) developed CKD (estimated glomerular filtration rate < 60 ml/min/1.73 m2 and/or proteinuria). The cumulative incidence of CKD was significantly higher among subjects who did not perform habitual exercise and hyperglycemic subjects (log-rank test: p < 0.05, respectively). According to a Cox proportional hazards model, the hazard ratio (HR) for the incidence of CKD in subjects with a normal glucose tolerance (NGT) who did not perform habitual exercise (HR = 2.82, 95% confidence of interval (CI) = 1.07-7.36, p = 0.034) and that in hyperglycemic subjects who did not perform habitual exercise (HR = 5.89, 95% CI = 1.87-16.63, p = 0.003) were significantly higher in comparison to the subjects with a NGT who performed habitual exercise. Conclusions These results suggest that the habitual exercise and good glycemic control and their combination were associated with the incidence of CKD.